Psychological morbidity among young adults attending primary care: a retrospective study. Issue 1 (15th October 2015) - Hickey, Louise; Hannigan, Ailish; O'Regan, Andrew; Khalil, Sherif; Meagher, David; Cullen, Walter
Abstract: Aim: Currently, Ireland has the fourth highest rate of youth suicide in the European Union with psychological morbidity ranging from 21% to 27% in young adults. Primary care is ideally situated to address mental health problems and provide direction and support to young adults. This study investigates the prevalence and management of young adults aged 18–25 presenting to their general practitioner with a psychological problem as part of a larger study on all adults. Methods: A random sample of 100 patients aged 18 and over with a consultation in the previous 2 years was selected from the practice management systems of 40 general practices in Ireland. Clinical records of active patients (excluding temporary visitors to the practice) were examined using a standardized reporting tool to extract information on demographics, prevalence, diagnoses and treatments for psychological problems. Results: Of the 3845 active patients sampled aged 18 and over, 479 were in the target age group of 18–25. Of the 479 young adults identified (51% female, 60% fee paying), 57 (12%, 95% CI: 9–15%) had a documented psychological problem within the previous 2 years. Those with psychological problems were more likely to be frequent attenders and eligible for free medical care. Depression (23%) and stress and anxiety (23%) were most commonly identified. Conclusions: The estimated prevalence rate is considerably lower than previous studies which may indicate reluctance among young adults in presenting to primary care or reflect under‐identification of psychological problems. Given the high rate of prescribing, enhancing access to non‐pharmacological treatments in primary care is a priority.